Factors Affecting The Integrity of Company Financial Statements - Restu Ardia Pramesti; Hexana Sri Lastanti (Jurnal Indonesia Sosial Sains, 2024)
This research aims to test and gather empirical evidence of Factors Affecting the Integrity of the Company's Financial Statements. Factors examined in this study include Audit Committee, Board of Commissioners, Institutional Ownership, Audit Tenure, Auditor Industry Specialization and Financial Distress as independent variables. Meanwhile, the dependent variable is the Integrity of Financial Statements. The sample chosen for this study is Consumer Goods Industry Sector Companies listed on the Indonesia Stock Exchange (IDX) during 2020-2022, then purposive sampling method was implemented as the sampling technique. This study uses secondary data: the company's financial statements and annual reports. The collected data were then analysed by multiple linear regression using Statistical Package for Social Sciences (SPSS) version 22. The study’s findings reveal that the Audit Committee positively affects the integrity of Financial Statements. Meanwhile, the Board of Commissioners, Institutional Ownership, Audit Tenure Auditor Industry Specialization, and Financial Distress do not affect the Integrity of Financial Statements. It is recommended that further research consider adding variables as independent variables, moderating variables or intervention variables that have the potential to increase their influence on the integrity of financial reports.